Couple Stress Effects on Peristaltic Transport of Peristaltic Flow of Carreau Fluid in an Inclined Asymmetric Channel with Porous Medium - Hamza Rashid Dana; Liqaa Z. Hummady (Ibn Al-Haitham Journal for Pure and Applied Sciences)
In this paper, we share a discussion of the Couple Tension Effect on the Peristaltic Transfer of Carreau Peristaltic Flow of Fluid in an Inclined Nonlinear Canal with aPorous Medium the Carreau model's constitutive equation is selected to represent solutions to these problems are obtained A numerical method has been used to answer the problems and consideration, such as perturbation method. Closed form dynamical plus stream function formulas efficiency are pressure was created increase per wave length has been estimated numerically on the channel walls. The Hartman digits impacts (Ha), Darcy digit (Da), amplitude ratio (e), and their consequences. The full effects of axial velocity and entrapment are carefully examined and graphically represented. Numerical results have been computed by using MATHEMATICA software for all these problems and scheming the graphs. At increasing B the velocity increases in the focal area withe border canal wall but the opposite occur for increasing (Da). And the axial velocity does not change with increasing of (Ha). The pressure of rice for each wavelength dalta P increases in magnitude with increasing values of (Ha).